2015
DOI: 10.1002/humu.22774
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Heterogeneity and Clinical Variability in Musculocontractural Ehlers-Danlos Syndrome Caused by Impaired Dermatan Sulfate Biosynthesis

Abstract: Bi-allelic variants in CHST14, encoding dermatan 4-O-sulfotransferase-1 (D4ST1), cause musculocontractural Ehlers-Danlos syndrome (MC-EDS), a recessive disorder characterized by connective tissue fragility, craniofacial abnormalities, congenital contractures, and developmental anomalies. Recently, the identification of bi-allelic variants in DSE, encoding dermatan sulfate epimerase-1 (DS-epi1), in a child with MC-EDS features, suggested locus heterogeneity for this condition. DS-epi1 and D4ST1 are crucial for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
127
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(136 citation statements)
references
References 37 publications
4
127
0
1
Order By: Relevance
“…Recently, a patient with a microdeletion on chromosome 6q25.1 was described with among other symptoms an Ehlers-Danlos syndrome in skin [45]. The microdeletion included the lack of human UST gene indicating that the minor sulfation of CS/DS affects also the organization of the extracellular matrix, similar to the DS [46]. Understanding the impact of Ust and 2-O sulfation might identify potential therapeutic targets in melanoma metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a patient with a microdeletion on chromosome 6q25.1 was described with among other symptoms an Ehlers-Danlos syndrome in skin [45]. The microdeletion included the lack of human UST gene indicating that the minor sulfation of CS/DS affects also the organization of the extracellular matrix, similar to the DS [46]. Understanding the impact of Ust and 2-O sulfation might identify potential therapeutic targets in melanoma metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…They are mainly characterized by skin hyperextensibility, articular hypermobility and tissue fragility. The condition also has a distinctive craniofacial component including micrognathia, high and/or cleft palate, brachycephaly, hypertelorism, downslanting palpebral fissures and low-set ears [98], [99]. It is caused by autosomal recessive loss-of-function mutations in genes encoding dermatan sulfate (DS) biosynthetic enzymes: dermatan 4-O-sulfotransferase 1 ( CHST14 ) or DS epimerase-1 ( DSE ).…”
Section: Craniofacial Disorders Modeled In Xenopusmentioning
confidence: 99%
“…Syx et al reported another family with a homozygous DSE missense variant (p.Arg267Gly) [43]. The clinical manifestations of the two affected adult sisters showed craniofacial dysmorphic features, congenital clubfeet, long and slender fingers with contracture, muscle weakness, smooth, hyperextensible, and translucent skin, and the formation of large hematomas.…”
Section: Human Disorders Affecting the Skeleton And Skin Caused Bymentioning
confidence: 99%
“…The clinical manifestations of the two affected adult sisters showed craniofacial dysmorphic features, congenital clubfeet, long and slender fingers with contracture, muscle weakness, smooth, hyperextensible, and translucent skin, and the formation of large hematomas. No obvious alteration in the architecture of collagen fibrils was detected in DSE-deficient patients [43]. In contrast, CHST14-deficient patients show collagen bundles with collagen fibrils of various diameters, the intermittent presence of small flower-like fibrils, and irregular spaces filled with granulofilamentous deposits [43].…”
Section: Human Disorders Affecting the Skeleton And Skin Caused Bymentioning
confidence: 99%
See 1 more Smart Citation